(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Goods and Services Tax (GST) is without question the most significant and far-reaching taxreform in India’s post-independence history. The Products and Services Tax (GST) was proposed in Indiawith the intention of creating a national sales tax that would apply equally to all goods and services soldinside the country. As a result of GST replacing other taxes (sales tax, service tax, etc.), the Indianeconomy is now more unified and more individuals are subject to taxation. It has the potential to greatlycontribute to the expansion of the economy and the nation’s wealth through increasing productivity.Perhaps never before in the modern tax history of the world has a new tax regime been implemented,ingrained in both products and services by the State and the center in such a broad and complicatedsystem. There were several disadvantages and restrictions with the previous indirect tax system. Thebenefits of GST were able to mitigate or completely offset the bulk of the drawbacks.In this Article theauthor has made an attempt to explore the benefits of introducing GST in India.